Pengaruh Lembaga Keuangan Mikro Agribisnis Terhadap Peningkatan Pendapatan Anggota Gabungan Kelompok Tani (Studi Pada desa Barebbo Kecamatan Barebbo) - Wahyuni Wahyuni; Firdaus Firdaus (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
This study discusses the effect of Agribusiness Microfinance Institutions on Increasing Income of Combined Farmer Group Members (Study in Barebbo Village, Barebbo Subdistrict). This study aims to find out (1) whether the Micro Agribusiness Financial Institution influences the increase in income of members of the Joint Farmer Group in the village of Barebbo. The results of the study showed that parking retribution on the side of public roads contributed significantly to local revenues only in 2013 because of the APAD MPAD, while parking fees on the side of public roads did not contribute significantly to local revenues in 2012, 2014, 2015 and 2016 due to APAD MPAD.